3-(4-Chlorophenyl)-2-methylacrylic acid - Muhammad, Niaz (International Union of Crystallography, 2008)
In the crystal structure of the title compound, C(10)H(9)ClO(2), dimers form as a result of intermolecular O—H⋯O bonding. These dimers are linked to each other via C—H⋯O bonds, where the CH group belongs to the benzene ring and the O atom is from the carbonyl group of an adjacent molecule. There exist two intermolecular C—H⋯O hydrogen bonds, which individually form five-membered rings. There also exists a π–π interaction between the aromatic ring and its symmetry counterpart, with a centroid–centroid distance of 4.0202 (17) Å, and a C—H⋯π interaction between a methyl CH group and the aromatic ring.